1997
DOI: 10.1038/nm0797-793
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic plants expressing autoantigens fed to mice to induce oral immune tolerance

Abstract: Oral administration of protein can induce antigen-specific immune hyporesponsiveness. However, the utility of oral tolerance to autoantigens in the treatment of autoimmune diseases may be limited when candidate autoantigens cannot be produced by conventional systems in quantities sufficient for clinical studies. Plants may be ideally suited for this purpose, as they can synthesize, glycosylate and assemble mammalian proteins to provide huge quantities of relatively low cost soluble proteins. Furthermore, edibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
3
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(73 citation statements)
references
References 21 publications
1
66
3
3
Order By: Relevance
“…We found that the production of IL-4 increased, whereas the production of IFN-γ decreased, indicating that the immunisation of NOD mice with rVV-GAD65 induced a Th2 immune response in an antigenspecific manner. Our finding is consistent with the results of previous reports on NOD mice treated with GAD protein systemically, nasally or orally [28,29,33,34,35] or vaccinated with GAD encoding plasmid DNA [41]. Th2 immune responses induced by rVV-GAD immunisation could play an important role in the prevention of autoimmune diabetes in this animal model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that the production of IL-4 increased, whereas the production of IFN-γ decreased, indicating that the immunisation of NOD mice with rVV-GAD65 induced a Th2 immune response in an antigenspecific manner. Our finding is consistent with the results of previous reports on NOD mice treated with GAD protein systemically, nasally or orally [28,29,33,34,35] or vaccinated with GAD encoding plasmid DNA [41]. Th2 immune responses induced by rVV-GAD immunisation could play an important role in the prevention of autoimmune diabetes in this animal model.…”
Section: Discussionsupporting
confidence: 93%
“…In Type I diabetes, GAD and insulin have been identified as major autoantigens and tolerisation against these autoantigens has been attempted as a method for the prevention of the disease [14,32]. It has been reported that administration of purified GAD protein or peptide or insulin protein or peptide to NOD mice by a variety of routes can tolerise the T cell-mediated immune response against pancreatic beta cells, resulting in the prevention or delay of the development of insulitis and diabetes [28,29,33,34,35,36,37,38,39]. In many cases, the preventive effect was found to be associated with a Th2 shift [14,32].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of target protein to total protein in our system was higher than that obtained from a previous study. 17 In this study, we chose the clone with the highest Der p2 expression level (Der p2 expressed in the cytosol) for the protein extraction. The amount of Der p2 from a total protein extraction of 35 g dry weight callus can be up to 0.185 g. The Der p2 expression in transgenic tobacco plant cells is shown in Figure 1c.…”
Section: Generation Of Transgenic Plantsmentioning
confidence: 99%
“…In addition, the exceptional stability of transgenic proteins allows for ease of storage and transportation. 17 Additionally, using plants to express recombinant proteins prevents production of unwanted byproducts such as endotoxin production, which can be produced from Escherichia coli expression systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a transgenic plant capable of synthesizing GAD in an immunogenic form has been described (91). One may speculate whether the oral administration of the putative autoantigen of SMS can induce protective immune responses in patients with SMS.…”
Section: Helfgottmentioning
confidence: 99%